THE RELATIONSHIP BETWEEN RELIGIOUS ORIENTATION AND PERCEIVED RISK OF HIV INFECTION IN MEMBERS OF THE MUSLIM COMMUNITY IN JOHANNESBURG, SOUTH AFRICA - Mahomed, Aqeela; Laher, Sumaya (New Voices in Psychology, 2016)
It has been suggested that Muslim individuals have significantly lower prevalence rates of the Human Immunodeficiency Virus (HIV) infection than other religious groups around the world. This is attributed to the strict adherence of Islamic laws that are seen to inhibit the disease. Therefore, this study sought to investigate the possibility of an association between religious orientations and the way in which this influences Muslim individuals’ perceptions of the likelihood of contracting the HIV infection. A questionnaire consisting of a religious orientation scale as well as a perceived risk scale was administered to Muslims in Lenasia, South of Johannesburg and surrounding areas. Results revealed correlations between intrinsic religious orientation and perceived risk. This remained the case after controlling for the age, gender, marital status and level of education of the participants. This means that the more Muslims rely on religion for guidance and religious tenets for personal gratification, the greater their awareness of their perceived risk to HIV.